2006
DOI: 10.1227/01.neu.0000190662.71046.66
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Magnesium Infusions Are Not Associated with Increased Pressor Requirements after Carotid Endarterectomy

Abstract: INTRODUCTION-Although magnesium provides cerebral protection in animal stroke models, magnesium therapy has significant side effects in humans. Therefore, we sought to examine the incidence of α-agonist treated hypotension in our ongoing, prospective, randomized, double-blind, placebo-controlled Phase I/IIa dose escalation study of magnesium therapy in patients undergoing carotid endarterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…151 The same group showed that the dose of MgSO 4 did not influence the requirement, duration, or amount of postoperative pressor support. 152 However, a truly neuroprotective effect of magnesium during carotid endarterectomy is difficult to claim because potential confounders such as residual effects of an-esthetics cannot be completely ruled out considering an observation period of only 24 h after surgery in that study.…”
Section: Experimental Datamentioning
confidence: 91%
“…151 The same group showed that the dose of MgSO 4 did not influence the requirement, duration, or amount of postoperative pressor support. 152 However, a truly neuroprotective effect of magnesium during carotid endarterectomy is difficult to claim because potential confounders such as residual effects of an-esthetics cannot be completely ruled out considering an observation period of only 24 h after surgery in that study.…”
Section: Experimental Datamentioning
confidence: 91%
“…A preliminary prospective dose escalation study in 80 patients undergoing elective carotid endarterectomy established that Mg and placebo groups had statistically significant different serum levels of Mg ( p < 0.01) and no significant difference in adverse events ( p = 0.66) ( 46 ). The neuroprotective effect of Mg in carotid endarterectomy was evaluated in a randomized, double-blinded, placebo-controlled study of 108 patients.…”
Section: Clinical Trials Of Magnesium Sulfate In Neurovascular Diseasmentioning
confidence: 99%